Chemical Composition and Enantiomeric Distribution of Volatile Components of Vitex trifolia Essential Oil - Mudianta, I Wayan; Apriani, Ni Putu; Dewi, Indah Kusuma; Ayuni, Ni Putu Sri (Chemistry Department, The University of Brawijaya, 2025)
This study addressed the need to fully characterized the chemical composition of Vitex trifolia essential oil by using both capillary non-chiral and chiral GC-MS column. Employing the same oven program, the essential oil was injected into a capillary non-chiral column (RTX5-MS) and a derivatized cyclodextrin based chiral column (Rt-βDEXse). Five major terpenes were identified from both columns including α-pinene, sabinene, eucalyptol, α-terpinyl acetate, and β-caryophyllene. Seventeen volatile components were identified from each column that can be grouped into monoterpenes, sesquiterpenes, and their oxygenated derivatives. The enantio-resolution of the oil indicated the presence of two pairs of enantiomers including (+)- and (˗)-sabinene (5.59% and 94.41%) as well as (˗)- and (+)-α-terpineol (22.35% and 77.65%). The full chromatographic characterization of the essential oil can serve as chemotaxonomic assignments for detecting adulteration and for indicating of genuineness.